Struktur Anatomis dan Perkembangan Putik Lili (Lilium longiflorum Thunb.) - , SITI HARIANTI, Dra. Siti Susanti, S.U ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lily (Lilium longiflorum Thunb.) is bulbous plant and commonly cultivated as cut flowers in Japan, America and the Netherlands. In Indonesia lily is one of the commodity cut flower potential to be cultivated by farmers. Improving the quality and quantity of seedling can be done by improving of plant quality. Lily reproduce by seeds and bulbs. Seeds are produced from fertilization. The anatomical structure of the female reproduction can be used to determine the growth and development of pistil. The purpose of this research was to investigate and study the anatomical structure of Lilium longiflorum Thunb. pistil and its development based on the size of the flower buds. Research materials were lily flower buds in various size. The flower buds of lily were obtained from Bandungan, Ambarawa, Jawa Tengah. Anatomical preparations in this research were done using paraffin method with single staining. The parameters observed were anatomical structure of pistil which are stigma and style. From the observation, it was found that the size of the flower buds does not affect the level of pistil development. There are papillae on the stigma surface to hold pollen. Papillae initially grow in lilies bud at the size of 6.8 cm. Cells of the smallest flower buds are meristem with big nucleus and thin wall. The flower buds are composed of parenchyma cells. Cells compose of stigma and style are parenchyma, where the size of stigma parenchyma are shorter than style parenchyma. Style of Lilium longiflorum Thunb. has stylar canal, so that style type of this spesies is a hollow style. There is one layer of epidermal cell, that compose the stylar canal.